2018
DOI: 10.1111/jcmm.13732
|View full text |Cite
|
Sign up to set email alerts
|

Aldolase A as a prognostic factor and mediator of progression via inducing epithelial–mesenchymal transition in gastric cancer

Abstract: Glycolysis is regarded as the hallmark of cancer development and progression, which involves a multistep enzymatic reaction. This study aimed to explore the clinicopathological significance and potential role of glycolytic enzyme aldolase A (ALDOA) in the carcinogenesis and progression of gastric cancer (GC). ALDOA was screened from three paired liver metastasis tissues and primary GC tissues and further explored with clinical samples and in vitro studies. The ALDOA protein level significantly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The ALDOA‐induced morphological changes were accompanied by suppression of the expression of adherens and tight junction proteins including E‐cadherin, β‐catenin, and JAM‐A (Figure 6), which has also been shown to occur during the EMT process 40 . As described above, ALDOA has been shown to be highly expressed in malignant neoplasia of various organs and to be involved in malignant behaviors of cancer cells; however, the underlying molecular mechanisms have not been fully elucidated 41,42 . We found that overexpression of ALDOA induced the expression of HIF‐1α, which is known to modulate EMT through regulation of EMT‐related transcription factors including Twist, Snail, Slug, Smad interacting protein 1 (Sip1), and zinc finger E‐box‐binding homeobox 1 (ZEB1) 43‐46 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The ALDOA‐induced morphological changes were accompanied by suppression of the expression of adherens and tight junction proteins including E‐cadherin, β‐catenin, and JAM‐A (Figure 6), which has also been shown to occur during the EMT process 40 . As described above, ALDOA has been shown to be highly expressed in malignant neoplasia of various organs and to be involved in malignant behaviors of cancer cells; however, the underlying molecular mechanisms have not been fully elucidated 41,42 . We found that overexpression of ALDOA induced the expression of HIF‐1α, which is known to modulate EMT through regulation of EMT‐related transcription factors including Twist, Snail, Slug, Smad interacting protein 1 (Sip1), and zinc finger E‐box‐binding homeobox 1 (ZEB1) 43‐46 .…”
Section: Discussionmentioning
confidence: 62%
“…40 As described above, ALDOA has been shown to be highly expressed in malignant neoplasia of various organs and to be involved in malignant behaviors of cancer cells; however, the underlying molecular mechanisms have not been fully elucidated. 41,42 We found that overexpression of ALDOA induced the expression of HIF-1α, which is known to modulate EMT through regulation of EMT-related transcription factors including Twist, Snail, Slug, Smad interacting protein 1 (Sip1), and zinc finger E-box-binding homeobox 1 (ZEB1). [43][44][45][46] In this study, we also confirmed that some of the transcription factors were increased by ALDOA overexpression (Figure 6) and they are probably responsible for downregulation of adherens and tight junction proteins (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect has been experimentally confirmed by over-expression of glycolytic enzymes accompanied by deficit in OXPHOS-mediated ATP production in many cancer types in both cultured cell lines and animal models [87,88]. Genes affected by HIF-1 and implicated in carcinogenesis include SCL2A solute carrier family and those encoding glycolytic enzymes such as hexokinase II (HK II), phosphofructokinase 1 (PFK1), fructose-bisphosphate aldolase A (ALDOA), α-enolase (ENO1), pyruvate kinase M2 (PKM2), and lactate dehydrogenase A (LDH-A or LDH-5), as well as genes encoding PDK and enzymes of PPP [89,90].…”
Section: Enhancement Of Glycolysismentioning
confidence: 99%
“…Likewise, for the three subsequent enzymes of glycolysis aldolase (ALDO), phosphoglycerate mutase (PGAM) and enolase (ENO), inhibiting phytochemicals found in nature are described [51][52][53][54][55]. ALDO reversibly cleaves FBP into glyceraldehyde-3-phosphate (G3P) and dihydroxyacetone phosphate (DHAP).…”
Section: Glycolysismentioning
confidence: 99%